2014
DOI: 10.1111/myc.12238
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcosis‐related deaths and associated medical conditions in the United States, 2000–2010

Abstract: Cryptococcosis is an invasive mycotic infection primarily affecting immunocompromised individuals. The objective of this study was to describe cryptococcosis mortality and associated medical conditions in the US for the period 2000-2010. Cryptococcosis-related deaths were identified from the national multiple-cause-of-death dataset. Mortality trends and comparison analyses were performed on overall cases of cryptococcosis and by subset [i.e. clinical manifestations of disease and human immunodeficiency virus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…In this mixed population in a low cryptococcal meningitis prevalence U.S.A setting —0.4–1.3 per 100,000 people [21] — the presence of cryptococcal serum antigen showed the highest sensitivity for detecting cryptococcal meningitis. Based on these findings, a positive serum test should prompt immediate evaluation of CSF and initiation of empirical cryptococcal meningitis therapies in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this mixed population in a low cryptococcal meningitis prevalence U.S.A setting —0.4–1.3 per 100,000 people [21] — the presence of cryptococcal serum antigen showed the highest sensitivity for detecting cryptococcal meningitis. Based on these findings, a positive serum test should prompt immediate evaluation of CSF and initiation of empirical cryptococcal meningitis therapies in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptococcosis is estimated to have an overall annual age-adjusted mortality of 0.07 per 100,000 population in 2010 in the U.S.A. [21]. Mortality is highly associated with HIV infection, cirrhosis, malignancy and autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, cryptococcal meningitis remains as the most common life‐threatening opportunistic fungal infection among HIV‐infected individuals with an estimated annual mortality of 625 000 persons, which ranks cryptococcosis as fourth among the most common infectious causes of death in sub‐Saharan Africa . In addition, it has been reported that up to 6% of people with impaired cellular immunity due to other causes, are at risk of developing clinically apparent infections due to Cryptococcus …”
Section: Introductionmentioning
confidence: 99%
“…For example, the trend presented by John Perfect at the ICCC was for decreased mortality in the HIV positive population in developed countries, but not amongst the “otherwise healthy” group. This is borne out by recent estimates of mortality rates in the United States, with 80% of people succumbing to the disease in the last 11 years not being HIV positive, in contrast to the early days of the AIDS pandemic (Barragan et al, 2014). …”
Section: Cryptococcosis As a Major Global Health Problemmentioning
confidence: 99%